Answer:
[tex]g(x) - f(x) = 3x - 8 - 5x[/tex] is the answer.
Step-by-step explanation:
Considering the parent functions
To Determine:
We have to determine
[tex]g(x) - f(x)[/tex]
To find the difference between two function, subtract the first from the second.
The difference of [tex]g-f[/tex]
[tex](g-f)(x)=g(x)-f(x)[/tex]
As
So,
[tex](g-f)(x)=g(x)-f(x)[/tex]
And
[tex]g(x) - f(x) = 3x - 9 - (5x - 1)[/tex]
Solving
[tex]3x-9-\left(5x-1\right)....[A][/tex]
As
[tex]-\left(5x-1\right)[/tex]
[tex]Distribute\:parentheses[/tex]
[tex]=-\left(5x\right)-\left(-1\right)[/tex]
[tex]\mathrm{Apply\:minus-plus\:rules}[/tex]
[tex]-\left(-a\right)=a,\:\:\:-\left(a\right)=-a[/tex]
[tex]=-5x+1[/tex]
So, equation [A] becomes
[tex]3x-9-\left(5x-1\right) = 3x-9-5x+1[/tex] ∵ [tex]-\left(5x-1\right):\quad -5x+1[/tex]
[tex]3x-9-\left(5x-1\right) = 3x-8-5x[/tex]
Therefore,
[tex]g(x) - f(x) = 3x - 8 - 5x[/tex] is the answer.
Keywords: combining functions, The difference of [tex]g-f[/tex]
Learn more about composition of function from brainly.com/question/12293021
#learnwithBrainly